(untitled) (REMUNOM, 2025)
Natural products, especially secondary metabolites of essential oils and plant extracts, have gained prominence in pharmacological research due to their therapeutic effects associated with a more favorable safety profile compared to benzodiazepines (BZDs), widely used in the treatment of anxiety. Among these compounds, limonene stands out, a monocyclic monoterpene abundant in species of the Rutaceae family, with the potential to modulate central neurotransmitters such as dopamine, serotonin, γ-aminobutyric acid (GABA) and glutamic acid, all related to the regulation of anxiety. This study evaluated the anxiolytic potential of limonene through molecular docking simulations with the GABAa receptor, comparing its results with those of diazepam. The Hex 8.0.0 software was used to perform the molecular docking between limonene and the GABAa receptor (PDB ID: 4COF), and the methodology was validated with an additional simulation of diazepam. Molecular interactions and ligand positioning in the binding sites were analyzed using PyMOL 1.4.7. The results demonstrated that limonene showed affinity and selectivity for the same binding site as diazepam in the GABAa receptor, suggesting anxiolytic activity mediated by this receptor. These findings indicate that limonene can act as a positive allosteric modulator, with effects similar to those of BZDs, but possibly with fewer adverse effects. Based on the above, it is concluded that limonene is a promising candidate for the development of anxiolytic therapies based on natural compounds. However, in vivo and clinical studies are essential to confirm its efficacy and safety. The combination of computational and experimental approaches can accelerate its validation and broaden the perspectives of modern pharmacognosy.